SPECIFIC CLINICAL COURSE OF ACUTE CORONARY SYNDROME IN YOUNG PEOPLE - Akhmedov Latif Abbosovich (International Engineering Journal For Research & Development, 2020)
Acute coronary syndrome is a serious life-threatening condition that often serves as the clinical debut of ischemic heart disease. In 20-25% of cases, angina pectoris begins with acute myocardial infarction and painful angina after acute myocardial infarction The high incidence of acute coronary syndrome in young people in recent years indicates that the disease is getting younger. From the point of view of modern knowledge, which is the gold standard in the treatment of acute coronary syndrome - modern pharmacological support is very important both before endovascular surgery and during percutaneous intervention.